Spatial correlations between summer ozone heatwave dual events and residents mental health in China - Rongjun Zeng; Jinhui Zhao; Yanxia Hu; Liling Chu; Shenwen Du; Changzhun Zheng; Chao He (Scientific Reports)
Abstract In the context of global warming, the frequency and intensity of extreme heat events have significantly increased. Elevated temperatures accelerate atmospheric photochemical reactions, resulting in higher ambient ozone (O3) levels. This convergence of heatwaves and elevated O2 concentrations presents a dual threat to public health. This study analyzes surface ozone concentrations and heatwave data from the summers of 2013 to 2020 across China, integrating these with mental health data from the Chinese population. Using spatiotemporal analysis and econometric models, we investigate the spatiotemporal dynamics of ozone and heatwaves during Chinese summers and assess population exposure risks. Our findings quantitatively elucidate the correlations between combined ozone-heatwave events and residents’ mental health. By 2020, the number of days with high surface ozone, heatwave days, and heatwave events in China had risen by 16.15%, 26.32%, and 15.67%, respectively, with marked spatial heterogeneity and clustering patterns. Despite a slight decline in 2020, the population exposed to high ozone levels (> 160 μg/m3) and prolonged heatwave conditions (> 20 days) showed an overall upward trend. Furthermore, 57.95% and 20.91% of regions are projected to remain at risk from these combined hazards. As surface ozone and heatwave exposure risks escalate, the mental health burden on residents has intensified, with significant spatial disparities observed.